Empowering speaking skills through problem-based learning in Indonesian blended classrooms - Jenny Ngo (Inovasi Kurikulum)
The COVID-19 pandemic accelerated the shift towards remote and blended learning, prompting educators to seek innovative pedagogical approaches. In response, the Indonesian government introduced the Merdeka curriculum, emphasizing student-centered learning, critical thinking, and independent knowledge-building. Problem-based learning (PBL) aligns well with these objectives, engaging students in real-world problem-solving and promoting critical thinking, collaboration, and communication skills. This study examines the effectiveness of PBL in enhancing English-speaking skills within a blended learning environment at a private university in Surabaya. Using a quantitative research approach, data were collected through classroom observations and surveys and analyzed with SPSS. The findings revealed that PBL effectively promoted self-directed learning, peer collaboration, and speaking skill development. These suggest that PBL is an effective strategy for enhancing language proficiency and fostering student engagement that aligns with Indonesia’s educational reforms. However, to further optimize PBL's effectiveness, it is recommended to consider adjustments such as flexibility for attendance, scaffolding for highly diverse students, and culturally relevant activities. These modifications can create a more inclusive and supportive learning environment for English Language Learners (ELLs) in Indonesia.